THE IMPORTANCE OF NEW TECHNOLOGIES IN FORMING HEALTHY LIFE STYLE OF STUDENTS AT PHYSICAL TRAINING LESSONS - Yakubjonova Feruzakhon Ismailovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article analyzes the main directions and tools used in the modern system of higher education, and notes the introduction of innovative technologies in teaching practice. Under such conditions, new forms and methods of physical activity at the lessons of physical education of university students can contribute to the formation of a healthy lifestyle.